Relationship Risk Factors and Hemiparesis Prevalence in Ischemic Stroke at Medical Rehabilitation Fatmawati General Hospital 2022 - Adril, Muhammad Alif; Lutfie, Syarief Hasan (The Avicenna Medical Journal, 2023)
Background: A stroke is a brain dysfunction in the form of nerve insufficiency caused by a disruption of blood flow to part of the brain. Stroke is divided into two types, namely ischemic and hemorrhagic type. Ischemic stroke or non-hemorrhagic stroke is an acute disease whose time of onset of symptoms determines the patient's survival prognosis. It will often cause cerebral infarction. The government of the Republic of Indonesia found that stroke patients, especially ischemic strokes in Indonesia, were still predominantly male, with a rate of 50,1%. This problem could be due to a more carefree lifestyle and a heavier workload. The stroke rate is very high and has increased dramatically, especially in patients >50 years of age. Methods: This study is a cross-sectional observational study. The study sample was obtained by a consecutive sampling of up to 105 study data samples taken from the medical record data. Data analysis was performed using univariate and bivariate analyses with Chi-Square tests. Results: Based on a sample of 105 patients, with an age range between 60-70 years old the following results Relationship of Prevalence of Hemiparesis in Ischemic Stroke Patients by Gender to Blood Pressure (P=0,312), Age (P=0,591) and Nutritional Status (P=0,760).Conclusion: No statistically significant relationship was found between stroke risk factors in blood pressure, age, and nutritional status with hemiparesis rates in geriatric ischemic stroke patients at the Medical Rehabilitation Clinic in Fatmawati Central General Hospital, Jakarta.